(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
In modern conditions, the human world is rapidly developing in a variety of aspects, including ontological, explaining the principles of being, axiological, giving an understanding of the theory of values, and epistemological, studying the process of knowing the world. In social science today, new categories are being formed that help us explain such phenomena. The processes taking place in society make the whole sphere around us change, as well as the spirit. In this movement, ideology acts as a mediator. There is a trend of transformation of social life and the spiritual component of our life. However, often such changes have a deformation. At the same time, one should not abandon the artificial promotion of ideas aimed at the formation of certain social behavior in society.